Are Inflationary Shocks Regressive? A Feasible Set Approach - Felipe Del Canto; John Grigsby; Eric Qian; Conor Walsh (The Quarterly Journal of Economics, 2025)
ABSTRACT We develop a framework to measure the welfare impact of macroeconomic shocks throughout the distribution. The first-order impact of a shock is summarized by the induced movements in agents’ feasible sets: their budget constraint and borrowing constraints. We combine estimated impulse response functions with micro-data on household consumption bundles, asset holdings, and labor income for different U.S. households. We find that inflationary oil shocks are regressive, but monetary expansions are progressive, and there is substantial heterogeneity throughout the life cycle. In all cases, the dominant channel is the effect of the shock on the cost of accumulating assets, not movements in goods prices or labor income.